KEDUDUKAN ANAK ANGKAT TERHADAP HARTA WARISAN DALAM PERSPEKTIF HUKUM ISLAM DI INDONESIA - Mona Eliza; Wildian Fajrin Nur Rahman (Jurnal Kommunity Online, 2023)
Children are part of all the hopes of both parents (father and mother) as a successor to life. Having children is the purpose of marriage to continue offspring and the preservation of wealth. Having children is the pride of the family. For couples who do not have children, many couples take other people's children to be adopted by couples who are not blessed with children. In Indonesia, there are three legal systems that apply and regulate the issue of child adoption. The three legal systems areIslamic Law, Customary Law and Legislation.